1984
DOI: 10.1071/mf9840187
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction annd development of Neosilurus ater (Perugia) and Neosilurus hyrtlii Steindachner (Teleostei : Plotosidae) in a tropical Queensland stream

Abstract: The reproduction and development of two plotosid catfishes, N. ater and N. hyrtlii, were investigated in a seasonal tributary of the Ross River, northern Queensland. The fishes were observed to move upstream to spawn during monsoonal flooding. Their mating behaviour, embryology and larval development are described. The adaptive significance of a flood-spawning strategy is discussed in relation to food availability, predation, and aeration in seasonal tropical streams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…The plotosid catfish (N. hyrtlii) may be the only obligate flood spawner, with recruitment restricted to the summer months after rising flows. Balcombe et al (2006) reported obligate flood spawning of this catfish in the dryland Warrego River (Murray-Darling Basin), and similar recruitment patterns have been reported in populations of N. hyrtlii from northern Australia (Orr and Millward, 1984;Pusey et al, 2004).…”
Section: Fish Life History and Recruitmentsupporting
confidence: 69%
“…The plotosid catfish (N. hyrtlii) may be the only obligate flood spawner, with recruitment restricted to the summer months after rising flows. Balcombe et al (2006) reported obligate flood spawning of this catfish in the dryland Warrego River (Murray-Darling Basin), and similar recruitment patterns have been reported in populations of N. hyrtlii from northern Australia (Orr and Millward, 1984;Pusey et al, 2004).…”
Section: Fish Life History and Recruitmentsupporting
confidence: 69%
“…Several other authors have suggested a strong relationship between rainfall and spawning in tropical fishes (e.g. Payne 1975, Orr & Milward 1984, Lowe-McConnell 1987, Ntiba & Jaccarini 1990.…”
Section: Discussionmentioning
confidence: 98%
“…For example, at 2 extremes, N. hyrtlii revealed breaks in the predicted regions, whereas N. ater showed a single clade across the entire AMT and New Guinea. These 2 species are similar in their ecology and dispersal behavior (Orr and Milward 1984). Thus, their strikingly different phylogeographic patterns are difficult to explain.…”
Section: Phylogeography and Conservation Of Freshwater Species In Thementioning
confidence: 99%